2012
DOI: 10.1002/jmor.20087
|View full text |Cite
|
Sign up to set email alerts
|

Gape size, its morphological basis, and the validity of gape indices in western diamond‐backed rattlesnakes (crotalus atrox)

Abstract: Maximum gape is important to the ecology and evolution of many vertebrates, particularly gape-limited predators, because it can restrict the sizes and shapes of prey that can be eaten. Although many cranial elements probably contribute to gape, it is typically estimated from jaw length or jaw width, or occasionally from a combination of these two measures. We measured maximum gape directly for 18 individuals of the western diamond-backed rattlesnake, Crotalus atrox. We measured each individual's body length, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 40 publications
1
28
1
1
Order By: Relevance
“…Specifically, adult N. fasciata increase gape size relatively quickly with increasing body size. This is a different relationship from that observed for the rattlesnake Crotalus atrox, in which there is no conspicuous change in slope between juveniles and adults (Hampton and Moon, 2013). The relatively steady rate of gape growth may be because C. atrox primarily consumes mammals regardless of size.…”
Section: Discussion Morphologycontrasting
confidence: 61%
See 4 more Smart Citations
“…Specifically, adult N. fasciata increase gape size relatively quickly with increasing body size. This is a different relationship from that observed for the rattlesnake Crotalus atrox, in which there is no conspicuous change in slope between juveniles and adults (Hampton and Moon, 2013). The relatively steady rate of gape growth may be because C. atrox primarily consumes mammals regardless of size.…”
Section: Discussion Morphologycontrasting
confidence: 61%
“…For instance, Aubret and colleagues (Aubret et al, 2004) found a disparity in the relative jaw length of two populations of tiger snakes, in which the population consuming larger prey had longer jaws. Hampton and Moon (Hampton and Moon, 2013) found that the slope of gape against SVL for a rattlesnake (Crotus atrox) was lower (0.57) and the intercept higher (0.43) than that for N. fasciata (slope=0.72, intercept=-0.12). This suggests that individuals of C. atrox have greater gape sizes for their body sizes, and that relative gape size does not increase as rapidly during growth in individuals of C. atrox compared with N. fasciata.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations